Proletarianization and Dispossession of Mixtec Workers: Roots of Indigenous Migration to New York - Rodolfo Hernández Corchado (Íconos)
This article analyzes the history of the formation of a transnational market of indigenous Mixtec workers from the region of Montañade Guerrero in New York. Based on ethnographic work with undocumented Mixtec workers in the United States, this article examines the formation of labor migration from the South of Mexico. This research traces the history of proletarianization and re-configuration of class hierarchies within the indigenous proletariat from Montañade Guerrero as the product of old and new forms of dispossession that have transformed this region into a new reserve of labor.